Digital media in ecuadorfuture perspectives - Punin Larrea, M. (2017)
The advances in technology, especially in the field of communication, cause mass media to constantly evolve- and thus not to perish. Indeed, this occurs in situations that are marked by a series of media transformations and changes that have affected journalism as a profession and mass media as a process. The studies that have resulted from these changes have been positive and negative. This paper analyses the digital media panorama in Ecuador, the characteristics of journalism culture and the specific usage of web content. It describes the trends of the main digital media in the country, which have been selected for a case study. The article takes as a core reference ten digital trends in media communication proposed by Cerezo-Gilarranza specialist in digital strategies. We then focus on the deficiencies of Ecuadorian mass media, which is mainly due to a lack of control over technological environments and the scarcity of links between business and journalism projects that have technological and innovative support, such as the usage of social networks and others. The final result is a detailed guide to the weaknesses and strengths of each digital medium that has been studied. Furthermore, this work highlights reliable trends so that the selected media can orientate towards digital environments. This is achieved by making use of technological tools for creating business and service opportunities